Texture, colour and sensory properties of non-fat yoghurt as influenced by tara gum or combinations of tara gum with buttermilk powder - Say, Dilek (Array, 2020)
The texture, colour and sensory properties of non-fat yoghurts prepared with different tara gum concentrations (0.25, 0.50 and 1.0 gL-1) and different tara gum (TG) with buttermilk powder (BP) combinations (0.25+10, 0.50+10 and 1.0+10 gL-1) were investigated during storage. While addition of 0.25 and 0.50 gL-1 of tara gum caused an increase in firmness, consistency, cohesiveness, viscosity index of yoghurt samples, use of 1 gL-1 of tara gum and combinations of tara gum with buttermilk powder led to a decrease in these properties. During the storage period, increasing the concentration of tara gum resulted in significant decrease in L* and a* values, significant increase in b* value in yoghurt. Sensory properties of non-fat yoghurts supplemented with 0.25 and 0.50 gL-1 did not significantly differ from those of control yoghurts. In contrast, use of 1 gL-1 of tara gum and combinations of tara gum and buttermilk powder caused a significant decrease of sensory properties of non-fat yoghurt.